POLA PEMBIMBINGAN DI TEMPAT KERJA: STUDI KASUS PELAKSANAAN PROGRAM PRAKTIK INDUSTRI DI PT JMI - Nuur Wachid Abdulmajid (Jurnal Taman Vokasi, 2015)
This research aims to know: patterns of supervision conducted by the supervisor of PI in the workplace. This research took place at PT. Jaringan Multimedia Indonesia (PT. JMI) as place for Industrial Practice Program. The key informants in this research were the industrial mentorsand students who participated in the industrial practice program. The data were collected through in-depth interviews, and documentation. The technical analysis of the data refered to the analysis of Miles & Huberman interactive model, including data collection, data condensation, data display, and drawing and verifying conclusions. The result shows that methods of supervision to students through mentoring that is focused on the handling of the case or case studies. So students are asked directly involved in work in the industry.